Effect of Three and Six Months of Vitamin D Supplementation on Glycemic Control and Insulin Resistance in Type 2 Diabetes Mellitus: Randomized Placebo-controlled Trial - Alvina Alvina; Suzanna Immanuel; Dante Saksono Harbuwono; Frans Dhyanagiri Suyatna; Alida Harahap; Joedo Prihartono; Pusparini Pusparini (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: 25(OH)D level is correlated with insulin secretion and tissue sensitivity to insulin. Administration of vitamin D supplements may reduce tissue resistance to insulin in type 2 diabetes mellitus (T2DM), but a number of studies found conflicting results. The present study was to measure the results of administration of vitamin D supplements for 3 and 6 months regarding HbA1c, fasting blood glucose (FBG), insulin and tissue resistance to insulin in T2DM cases.METHODS: A randomized double-blind placebo-controlled trial was conducted in T2DM patients with ≤3 years duration. Subjects were randomly divided into two groups: 47 subjects received daily 5000 IU vitamin D supplementation and 47 subjects received daily placebo as control. After supplementation for 3 and 6 months, homeostatic model assessment for tissue resistance to insulin (HOMA-IR), insulin, HbA1c, and FBG were examined.RESULTS: Supplementation of daily 5000 IU vitamin D for 3 months increased 25(OH)D level in the vitamin D group from 12.50±5.28 to 43.57±17.14 ng/mL, and after 6 months the 25(OH)D level was 38.38±17.64 ng/mL. Both groups showed significant differences after 3 and 6 months regarding HOMA-IR (p=0.033 and p=0.031), insulin (p=0.034 and p=0.013), but not FBG (p=0.296) and HbA1c (p=0.360). In both groups, HOMA-IR and insulin increased although the increase in the control group was greater than in the vitamin D group. The difference between the control and vitamin D groups was significant.CONCLUSION: Vitamin D supplementation for 3 and 6 months may lead to improvement HOMA-IR but not for FBG and HbA1c in the vitamin D group as compared with the control group in T2DM cases.KEYWORDS: vitamin D, T2DM, HbA1c, blood glucose, insulin, tissue resistance to insulin